(untitled) (Bioagro, 2022)
Prescribed burning of cattails is a frequent practice in coastal areas of Lake Titicaca in order to eliminate senescent biomass, obtain tender shoots and better nutritional quality as forage. Therefore, objective of the study was to determine effects of these burns on the nutritional value of aerial cattail stems, through proximal analyzes after burning for two consecutive years, comparing with cattails without burning for five years, in three phenological periods (sprouting, growth, and maturation), submitting the data under Anova with factorial arrangement 2*3 (two treatments, and three seasons) and Tukey’s test. According to results, dry matter in cattails with burning increased significantly (P<0,05) in relation to cattails without burning (27,02% ± 0,61 vs. 21,22% ± 1,06), achieving even higher values during sprouting and maturity, similarly the crude fiber had significant increase with consecutive burning (30,04% ± 2,81 vs. 28,13% ± 2,06), with higher concentrations during growth and maturity, while crude protein decreased due to effect of fire from growth period (7,34 % vs. 10,14 %), although with superiority ephemeral during sprouting (9,28 % vs 6,87 %) regarding cattail without burning (P<0,05). Consecutive prescribed burning affected the forage quality of cattail culms, reducing levels of proteins, nutrients of high biological value, but favoring an increase in dry matter, and fiber, which could affect their proper digestibility.